Updated Analysis of Mercury Complex solution with Rhodamine-B and Spectrophotometric Determination of Trace Amounts of Mercury in Wastewater - Gao, Hong-Weng (Asian Journal of Chemistry, 2010)
β-correction principle has been applied for the determination of mercury complex characteristics with rhodamine B (RDB) in the presence of iodide and in acidic solution, for example, complexation ratio, true molar absorptivity and stability constant. In addition, the determination of trace amounts of mercury in wastewater was analyzed. The results showed that the formed complex was Hg(RDB)3In, the cumulative stability constant Kc was equal to 3.55 x 1016 and its true (not apparent) molar absorptivity ε = 1.61 X 105 1 mole-1 cm-1. Beer's law was obeyed for 0-1.0 mg/L mercury. This method has been satisfactory for the determination of mercury in wastewater.